A healthful plant-based diet can reduce the risk of developing colorectal cancer: case-control study - Sazin Yarmand; Bahram Rashidkhani; Arezoo Alimohammadi; Zainab Shateri; Mahboobeh Shakeri; Zahra Sohrabi; Mehran Nouri (BMC, 2024)
Abstract Introduction The benefit of adherence to a plant-based diet concerning colorectal cancer (CRC) has not been investigated among Middle Eastern population. This study aimed to investigate how adherence to a plant-based diet influences the risk of CRC in this understudied population. Methods This case-control study was conducted in the CRC surgery departments of general hospitals in Tehran, Iran. A total of 71 individuals with newly diagnosed CRC (cases) and 142 controls subjects free of cancer and acute illness were concurrently recruited from the same hospital. Dietary information was collected using a semi-quantitative 168-item food frequency questionnaire. Dietary patterns were characterized using the plant-based diet index (PDI), unhealthy plant-based diet index (uPDI) and healthy plant-based diet index (hPDI). Multivariate logistic regression was employed to assess the association between these dietary patterns and the risk of CRC. Results After adjusting the potential confounders, the risk of CRC was significantly lower in the highest tertile of hPDI compared to the lowest tertile (odds ratio (OR) = 0.21; 95% confidence interval (CI): 0.07-0.56, representing 79% risk reduction). Conversely, the risk of CRC was significantly higher in the highest tertile of uPDI compared to the lowest tertile (OR = 6.76; 95% CI: 2.41-18.94). PDI was no significant associated with the risk of CRC. Conclusions This study found that higher scores on the hPDI was significantly associated with a decrease risk of CRC, while greater adherence to the uPDI contributed to a significantly increase risk.